Financial Ratios Analysis in Determination of Bank Performance in the German Banking Sector - Lardic, Sandrine; Terraza, Virginie (International Journal of Economics and Financial Issues, 2019)
This paper uses dynamic panel data methods to examine the determinants of bank’s performance in the German banking sector. The main determinants considered are indicators of solvency and liquidity, which makes it possible to observe the behavior of the banks in terms of risk before and during the financial crisis. The study is motivated by the hypothesis that the behavior of German banks depends on bank-specific variables which have an effect on loan policy of institutions. Universal banks in Germany can be divided into three main types of institutions: commercial, public-sector and cooperative banks. The analysis is conducted in a disaggregated manner by classifying the banks into main categories. Each category is examined separately so as to detect possible similarities or differences in the behavior of each panel on banks’ performance. The empirical analysis relates to a sample of 1624 German banks observed over the period 2000-2014. Keywords: Banking profitability, financial crisis, financial market structure. JEL Classifications: D21, G21, E44, C23, G32, L25 DOI: https://doi.org/10.32479/ijefi.7888